DETERMINAN KEPARAHAN KARIES BERDASARKAN INDEKS PUFA/pufa PADA ANAK SEKOLAH DASAR: STUDI CROSS-SECTIONAL DI WILAYAH KERJA PUSKESMAS TERMINAL BANJARMASIN - Riky Hamdani; Latifah Aini; Selena Mei Sesha; Salma Alifa (Dentin, 2026)
Background: Untreated dental caries frequently progresses to pulp and periapical complications in school-age children. Data from Terminal Primary Health Center Banjarmasin (2022–2024) showed pulp and periapical disease reaching 61.63% of all dental cases in 2024, indicating low early dental care awareness. Purpose: To analyze the relationship between dental caries knowledge, local breakfast consumption patterns, snack consumption frequency, and tooth care practices with caries severity based on the PUFA/pufa index among primary school children. Methods: An observational analytic cross-sectional study was conducted at SDN Sungai Lulut 8 Banjarmasin involving 60 students (grades 5–6) recruited by convenience sampling. Data were collected via self-administered questionnaire and direct oral examination using the PUFA/pufa index. Bivariate analysis used Spearman's rank correlation test (p < 0.05). Results: Mean PUFA/pufa score was 2.37 (moderate), with pulp involvement (P/p) as the predominant component (mean 1.98). Three variables showed significant correlations: dental caries knowledge (r = −0.356, p = 0.005), local breakfast consumption patterns (r = −0.295, p = 0.022), and tooth care practices (r = −0.547, p = 0.000). Snack consumption frequency showed no significant correlation (r = −0.032, p = 0.809). Conclusion: Among all behavioral factors examined, tooth care practices demonstrated the strongest correlation with caries severity, followed by dental caries knowledge and local breakfast consumption patterns, while snack consumption frequency showed no significant association. School-based interventions focusing on proper brushing habits, health literacy, and dietary modification are strongly recommended.Keywords: Dental caries severity, Dietary habits, Oral hygiene, Primary school children, PUFA/pufa index knowledge1.        Zero DT, Zandona AF, Vail MM, Spolnik KJ. Dental caries and pulpal disease. Dent Clin North Am. 2011;55(1):29–46. 2.        Teh LA, Abdullah D, Liew AKC, Soo E. Evaluation of pulpal involvement, ulceration, fistula, and abscess index and periapical index in screening for endodontic disease: reliability and accuracy. J Endod. 2020;46(6):748–755. 3.        Monse B, Heinrich-Weltzien R, Benzian H, Holmgren C, van Palenstein Helderman W. PUFA index: clinical consequences of untreated dental caries. Int Dent J. 2010;60(3):157–162. 4.        Saquicela-Pulla M, Dávila-Arcentales M, Vélez-León E, Armas-Vega A, Melo M. Parental knowledge, attitudes, and practices and their association with dental caries in children aged 5–9 years: a cross-sectional study in rural Ecuador. Int J Environ Res Public Health. 2025;22(6):953. 5.        Aulia F. Hubungan pengetahuan serta sikap tentang pemeliharaan kesehatan gigi dan mulut dengan pengalaman karies gigi pada siswa kelas VII SMP Plus Ulil Albab Depok Kabupaten Cirebon [skripsi]. Tasikmalaya: Politeknik Kesehatan Tasikmalaya; 2023. 6.        Kartikasari HY, Nuryanto N. Hubungan kejadian karies gigi dengan konsumsi makanan kariogenik dan status gizi pada anak sekolah dasar (studi pada anak kelas III dan IV SDN Kadipaten I dan II Bojonegoro). J Nutr Coll. 2014;3(3):414–421. 7.        Rahman E, Ilmi MB, Anam K. Kebiasaan mengkonsumsi jajanan kariogenik sebagai penyebab karies gigi pada anak di Madrasah Diniyah Islamiyah Muhammadiyah Kindaung Banjarmasin. J Kesehatan Indonesia. 2018;9(1):34–37. 8.        Assegaf Y. Hubungan pengetahuan dan perilaku kesehatan gigi mulut pada anak usia 10–11 tahun terhadap nilai indeks PUFA/pufa di SDN Tunjungsekar 03 Malang [skripsi]. Malang: Universitas Brawijaya; 2015. 9.        Rusmali R, Sartika M, Herlina R. Pengaruh menyikat gigi terhadap indeks DMF-T, status kebersihan gigi dan mulut (OHI-S) dan jenis makanan kariogenik. J Ilm Glob Educ. 2024;5(2):1120–1125. 10.     Sugiyono. Metode penelitian kuantitatif, kualitatif, dan R&D. Bandung: Alfabeta; 2018. 11.     Keumala CR. Hubungan pola makan dengan karies gigi pada murid sekolah dasar. J SAGO Gizi dan Kesehatan. 2020;1(2):146–151. 12.     Kurt A, Bolat D, Hatipoğlu Ö. Impact of the severity and extension of dental caries lesions on Turkish preschool children's oral health-related quality of life: a cross-sectional study. BMC Oral Health. 2025;25(1):210. 13.     Sharna N, Ramakrishnan M, Samuel V, Ravikumar D, Cheenglembi K, Anil S. Association between early childhood caries and quality of life: early childhood oral health impact scale and PUFA index. Dent J. 2019;7(4):95.